The Council of Europe's Modernized Convention on Personal Data Protection: Why Canada should consider accession - Colin J. Bennett (Centre for International Governance Innovation (CIGI), 2020)
Canada has much to gain by joining the Council of Europe's Modernized Convention on Personal Data Protection (Convention 108+), based on its predecessor, the Convention for the Protection of Individuals with regard to Automatic Processing of Personal Data. The latter remains the only binding international convention within the international privacy and data protection policy space. By joining Convention 108+, Canada would enhance its reputation as a trusted jurisdiction for personal data processing and its commitment to international privacy rights.
Keywords: 330; Data Protection; International Agreement; International Commercial Law; Canada; Datenschutz; Internationales Abkommen; Internationales Handelsrecht; Kanada